2017
DOI: 10.4103/1742-6413.200935
|View full text |Cite
|
Sign up to set email alerts
|

Detection of BRAF mutation in the cytocentrifugation supernatant fluid from fine-needle aspiration of thyroid lesions may enhance the diagnostic yield

Abstract: Objective:BRAF mutations using cellular DNA from fine-needle aspiration (FNA) specimens are commonly used to support the diagnosis of papillary thyroid carcinoma (PTC). The goal of this study was to preliminarily evaluate the diagnostic utility of detecting BRAF mutations in the routinely discarded FNA specimen supernatant fluid.Materials and Methods:Seventy-eight FNAs of thyroid lesions were evaluated for BRAF mutations using both cellular and supernatant DNA. BRAF mutation data were correlated with cytology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 23 publications
1
14
0
Order By: Relevance
“…Recent studies have reported on the feasibility of using residual liquid‐based cytology from thyroid FNA samples to perform molecular testing; this is akin to human papillomavirus testing from residual liquid‐based cytology in cervical cytology samples . A recent study has reported the detection of BRAF mutations by pyrosequencing in a subset of supernatants from FNA centrifuged needle rinses of thyroid nodules . In this study, we show that previously discarded supernatants from thyroid FNA needle rinses can provide substantial amounts of DNA for comprehensive mutational profiling by NGS for multiple genes, even when the corresponding FNA smear/cell block material is sparsely cellular and precludes further molecular testing.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Recent studies have reported on the feasibility of using residual liquid‐based cytology from thyroid FNA samples to perform molecular testing; this is akin to human papillomavirus testing from residual liquid‐based cytology in cervical cytology samples . A recent study has reported the detection of BRAF mutations by pyrosequencing in a subset of supernatants from FNA centrifuged needle rinses of thyroid nodules . In this study, we show that previously discarded supernatants from thyroid FNA needle rinses can provide substantial amounts of DNA for comprehensive mutational profiling by NGS for multiple genes, even when the corresponding FNA smear/cell block material is sparsely cellular and precludes further molecular testing.…”
Section: Discussionmentioning
confidence: 73%
“…The main concern regarding the use of supernatants from centrifuged FNA samples as a substrate for molecular analysis is the lack of a morphologic correlate that accounts for the tumor fraction in the sample. A recent study reported detecting BRAF mutations in FNA cytologic specimens but not in the corresponding centrifuged supernatant in a subset of its cases . However, the testing methodologies for the FNA cellular material and the supernatant material used in that study were different, and the difference in the analytic sensitivity of the 2 platforms used could explain the discordance seen in the paired samples.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…To overcome the limitations of the FFPE CB and to better preserve the remaining tissue in the CB, various alternative tissue‐containing materials, such as smeared slides and liquid samples, have been studied . Several institutions have reported the successful use of FNA supernatant fluid (SN) for molecular testing . In the current study, we examined the use of traditionally discarded CytoLyt (Hologic Inc) SN for DNA‐based and RNA‐based NGS molecular testing and compared its performance with that of paired FFPE CB material.…”
Section: Introductionmentioning
confidence: 99%
“…However, due to the multitude of biomarkers requested, the limited volume tissue available on the cytology slides may not always be adequate. Recent studies have shown that substantial amounts of nucleic acid can be retrieved from the supernatant fluid of fine needle aspiration needle rinses after centrifugation and cell pelleting [23][24][25][26][27]. In routine clinical workflow, this supernatant fluid is typically discarded; however tumor DNA that may be left in this fluid can be effectively utilized for characterizing molecular changes in tumor.…”
Section: Introductionmentioning
confidence: 99%